IMPACT OF GOOD CORPORATE GOVERNANCE PRACTICES ON TRANSPARENCY AND FIRM FINANCIAL PERFORMANCE – A GLOBAL PERSPECTIVE - Dr. Samadhi , Dilli; Tursunqolov , Inom (Scientific practical conference, 2025)
Corporate scandals, often driven by corruption, fraud, and mismanagement and have repeatedly undermined national economies and destroyed shareholders wealth. Weak corporate governance may leads to lost investor trust, impairs transparency, and ultimately damages firm performance. This paper examines major global corporate scandals and evaluates their impact on firms’ financial stability. It highlights the need for stronger corporate governance practices to enhance accountability, financial transparency, and long-term sustainability.